FEEDING BULLS FROM 6 MONTHS TO 10 MONTHS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Today, livestock accounts for 42% of the total agricultural output.in 2015, 2.0 mln. tons of meat, 8.9 mln. tons of milk, produced. this is 40 kg of meat and 276 kg of milk per person. significant results are also being achieved in the cultivation of other types of livestock products.in the development of animal husbandry in our country, the president of the republic of uzbekistan no. 308 of march 23, 2006, no. 842 of april 21, 2008 and the decree of december 29, 2015 "on measures to further reform and develop agriculture" resolutions no. pq-2460 serve as a program.